MUSSEL POLLUTION AT KORAPUZHA ESTUARY (MALABAR), WITH AN ACCOUNT OF CERTAIN COLIFORM TYPES - Venkataraman, R; Sreenivasan, A (Indian Journal of Fisheries, 2016)
OYSTERS, mussels and other shell-fish are highly nutritious foods, which,apart from their usual proximate principles, contain fairly high amountsof minerals Uke iodine, copper, iron, etc., and vitamins. In the shallow rockyareas of Malabar Coast there are numerous green mussel (Mytilus edulis)beds from which large quantities of mussels are taken out almost throughoutthe year, which form an important item of food for people of low incomes.As the mussels grow in shallow areas subject to the influence of land drainage,sewage and river systems, these beds constitute a potential hazard topubUc health on account of possible epidemic infections being carried bythe shell-fish